Bilateral cataract, crash risk, driving performance, and self‐regulation practices among older drivers. Issue 5 (May 2016) - Agramunt, Seraina; Meuleners, Lynn B.; Fraser, Michelle L.; Morlet, Nigel; Chow, Kyle C.; Ng, Jonathon Q.
Abstract : N/A: This comprehensive literature review summarizes published studies examining cataract and cataract surgery and driving outcomes to identify gaps in the literature that require further research. Six electronic databases were searched for articles published up to and including March 2015. Articles were reviewed if they included older drivers with cataract or drivers who had cataract surgery and at least 1 of the following driving outcomes: crash risk, driving self‐regulation practices, and driving performance. There was consistent evidence that cataract negatively affects driving and that cataract surgery is beneficial to driving outcomes. Future research should examine the separate effects of first‐ and second‐eye cataract surgery on crash risk, driving self‐regulation, and driving performance. It should also determine how visual measures relate to driving performance among cataract patients so those most at risk for driving difficulties can be identified, advised, and possibly prioritized for surgery. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.